PELAKSANAAN KEWENANGAN JAKSA PENGACARA NEGARA DI BIDANG TATA USAHA NEGARA PADA KEJAKSAAN TINGGI RIAU - Mulfanny Vania Zulhas; Ledy Diana; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The Attorney General’s Office of the Republic of Indonesia as regulated in LawNumber 16 of 2004 concerning the Prosecutor’s Office of the Republic of Indonesia is agovernment institution that carries out state duties in the field of prosecution and otherauthorities based on law. Where one of his duties is in the field of Civil and StateAdministration where the prosecutor with special powers can act both inside and outside thecourt for and on behalf of the state or government which is referred to as the State Attorney.In practice, the task as state attorney in handling State Administrative dispute cases can alsobe carried out by lawyers who are advocates. During the last three years, there have onlybeen two cases of State Administrative disputes handled by the State Attorney of the RiauHigh Court. So that the writing of this thesis aims to determine the criteria for StateAdministrative cases that can be handled by the State Attorney in the field of StateAdministration at the Riau High Court and to find out how the implementation of theauthority of the State Attorney in the State Administration at the Riau High Court.This type of research can be classified in the type of sociological research which iscarried out by direct research on the place under study to provide a complete and clearpicture of the problem being studied. This research was conducted in the High Service Officeof Riau, while the population and the sample are the parties related to the problem studied inthis study. The data sources used are; primary data, secondary data, and tertiary data, thedata collection techniques in this study were methods and interviews and literature study.From the results of this study, two conclusions can be drawn. First, cases or StateAdministrative disputes that can be handled by the Riau High Court. Second, this studydiscusses the implementation of the authority of the State Attorney at the Riau High Court.The researcher’s suggestions are, firstly, there is a correction of the prosecutor’s duties andauthorities in the field of state administration. Second, the provisions on the separation ofauthority are clearer for State Attorneys in both the Civil and State Administration scope.Third, strict provisions to be addressed to government agencies, state institutions,BUMN/BUMD to cooperate using the services of a State Attorney when there is a stateadministrative dispute.Keywords: Public Prosecutor – State Lawyer – Authority